Epidemiology of SARS-CoV-2 - Salzberger, Bernd; Buder, Felix; Lampl, Benedikt; Ehrenstein, Boris; Hitzenbichler, Florian; Holzmann, Thomas; Schmidt, Barbara; Hanses, Frank (Infection, 2021)
Purpose SARS-CoV-2 is a recently emerged ß-coronavirus. Here we present the current knowledge on its epidemiologic features. Methods Non-systematic review. Results SARS-CoV-2 replicates in the upper and lower respiratory tract. It is mainly transmitted by droplets and aerosols from asymptomatic and symptomatic infected subjects. The consensus estimate for the basis reproduction number (R 0 ) is between 2 and 3, and the median incubation period is 5.7 (range 2–14) days. Similar to SARS and MERS, superspreading events have been reported, the dispersion parameter (kappa) is estimated at 0.1. Most infections are uncomplicated, and 5–10% of patients are hospitalized, mainly due to pneumonia with severe inflammation. Complications are respiratory and multiorgan failure; risk factors for complicated disease are higher age, hypertension, diabetes, chronic cardiovascular, chronic pulmonary disease and immunodeficiency. Nosocomial and infections in medical personnel have been reported. Drastic reductions of social contacts have been implemented in many countries with outbreaks of SARS-CoV-2, leading to rapid reductions. Most interventions have used bundles, but which of the measures have been more or less effective is still unknown. The current estimate for the infection’s fatality rate is 0.5–1%. Using current models of age-dependent infection fatality rates, upper and lower limits for the attack rate in Germany can be estimated between 0.4 and 1.6%, lower than in most European countries. Conclusions Despite a rapid worldwide spread, attack rates have been low in most regions, demonstrating the efficacy of control measures.